Addiction and mood disorders - Daley, Dennis C. (Oxford University Press, 2006)
Addiction and Mood Disorders: A Guide for Clients and Families is designed primarily to educate individuals with dual disorders and their families about mood and addictive use disorders. It not only gives a message of hope, but also provides practical suggestions on ways to manage these disorders. The author provides guidelines and strategies for recovery from dual disorders based on, and adapted from various treatments that have proven effective for addiction, mood disorders, or both. This book is filled with case examples that show growth and positive change, as well as the difficulties many individuals struggling with a dual diagnosis face. Advocating a recovery model in which the affected individual takes responsibility for getting the most out of professional treatment and self-help programs, this book shows that being an active participant is the key to getting the most out of your recovery